Robust SERS Platforms Based on Annealed Gold Nanostructures Formed on Ultrafine Glass Substrates for Various (Bio)Applications - Zhou L; Poggesi S; Casari Bariani G; Mittapalli R; Adam P-M; Manzano M; Ionescu RE (MDPI (Basel, Switzerland), 2019)
In this study, stable gold nanoparticles (AuNPs) are fabricated for the first time on commercial ultrafine glass coverslips coated with gold thin layers (2 nm, 4 nm, 6 nm, and 8 nm) at 25 °C and annealed at high temperatures (350 °C, 450 °C, and 550 °C) on a hot plate for different periods of time. Such gold nanostructured coverslips were systematically tested via surface enhanced Raman spectroscopy (SERS) to identify their spectral performances in the presence of different concentrations of a model molecule, namely 1,2-bis-(4-pyridyl)-ethene (BPE). By using these SERS platforms, it is possible to detect BPE traces (10-12 M) in aqueous solutions in 120 s. The stability of SERS spectra over five weeks of thiol-DNA probe (2 µL) deposited on gold nano-structured coverslip is also reported.
(c) The Author/s
Keywords: BPE; SERS on ultrafine solid supports; annealed gold nanostructures; glass coverslips; thiol-DNA probe; Biosensing Techniques; DNA Probes; Glass; Gold; Indoles; Metal Nanoparticles; Particle Size; Spectrum Analysis, Raman; Surface Properties; Temperature; 0301 Analytical Chemistry; 0601 Biochemistry and Cell Biology